USSR Report, Earth Sciences. - JOINT PUBLICATIONS RESEARCH SERVICE ARLINGTON VA (1985)
This USSR report contains articles on Earth Sciences. The main topics are Meteorology, Oceanography, Terrestrial Geophysics, Physics of Atmosphere, arctic and Antarctic Research.